Aflibercept for Radiation Maculopathy (ARM Study): Year-2 Extension of a Prospective Clinical Study. (May 2021) - Murray, Timothy G.; Latiff, Azeema; Villegas, Victor M.; Gold, Aaron S.
Purpose: This work describes the 2-year results of the Aflibercept for Radiation Maculopathy (ARM) randomized clinical study that evaluated intravitreal vascular endothelial growth factor antagonist therapy in radiation maculopathy delivering aflibercept using a second-year collapsed, every-6-weeks, treat-and-adjust interval. Methods: Forty patients were enrolled in an institutional review board–approved clinical trial and randomly assigned to aflibercept treatment via 1 of 2 regimens: fixed, every-6-week treatment or variable, treat-and-adjust therapy centered around 6 weeks. All patients had a diagnosis of treated uveal melanoma with documented tumor control, and they had visually compromising radiation maculopathy. At conclusion of year 1, the first 30 patients were offered a collapsed single-arm variable of an every-6-weeks treat-and-adjust aflibercept injection schedule for an additional treatment year. Results: Baseline best-corrected visual acuity (BCVA) was 20/63 at ARM study entry 20/62 at the institution of the year-2 extension. At ARM study entry baseline, spectral domain–optical coherence tomography mean central retinal thickness was 432 µm and was 294 µm at the same institution. At the 2-year study's conclusion, 76.7% (23 of 30) of eyes were better than 20/50, and only 6.7% (2 of 30) ended with a BCVA below 20/200. Final mean BCVA was 20/62 and final mean spectral domain–optical coherence tomography central retinal thickness was 286 µm, but as in year 1, this reduction in number of injections was not statistically significant. Conclusions: Aflibercept is effective in treating radiation maculopathy with maintained visual acuity at 2 years but continues to require an ongoing treatment approach to stabilize radiation maculopathy.